Sport management research - an integral part of sport science? - Schnitzer, M.; Kopp, M. (Current Issues in Sport Science, 2018)
CURRENT ISSUES IN SPORT SCIENCE (CISS) has published in the last year 50% of the research articles in the section `sociology & economics`. The topics of these recently published articles in CISS show the importance and diversity of this area of research. The growing body of research in sport management has demonstrated that this scientific field has become a relevant piece in the interdisciplinary mosaic of sport science. In the future, these contributions might lead to an increase of sport management divisions within the departments of sport science to satisfy the growing demand of sport management related education.